Characterization of human αβTCR repertoire and discovery of D-D fusion in TCRβ chains - Liu, Peipei (Higher Education Press, 2014)
The characterization of the human T-cell receptor (TCR) repertoire has made remarkable progress, with most of the work focusing on the TCRβ chains. Here, we analyzed the diversity and complexity of both the TCRα and TCRβ repertoires of three healthy donors. We found that the diversity of the TCRα repertoire is higher than that of the TCRβ repertoire, whereas the usages of the V and J genes tended to be preferential with similar TRAV and TRAJ patterns in all three donors. The V-J pairings, like the V and J gene usages, were slightly preferential. We also found that the TRDV1 gene rearranges with the majority of TRAJ genes, suggesting that TRDV1 is a shared TRAV/DV gene (TRAV42/DV1). Moreover, we uncovered the presence of tandem TRBD (TRB D gene) usage in ~2% of the productive human TCRβ CDR3 sequences. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13238-014-0060-1) contains supplementary material, which is available to authorized users.